Analisis Perbedaan Model Belajar Peserta Didik Asrama dan Non-Asrama di Pondok Pesantren Putri Yatama Mandiri Gowa - Gani, Abd; Amaliyah, Nur Immawati (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Students in Islamic boarding schools have different learning environments, either living in dormitories or outside, which can influence their learning models and outcomes. This study aims to examine the differences in learning models and learning outcomes between dormitory and non-dormitory students at Pondok Pesantren Putri Yatama Mandiri Gowa. The research employed a qualitative method with data collected through observation, interviews, and documentation. The findings indicate that both groups apply similar learning models to those in general schools; however, dormitory students receive additional lessons through extracurricular activities outside regular school hours. Overall, both groups achieve good and satisfactory learning outcomes, but dormitory students excel in memorization and additional religious subjects. These findings imply the need for equitable learning strategies for all students, as well as specific support for subjects perceived as difficult, such as mathematics, English, and memorization.